Melatonin-Pretreated Mesenchymal Stem Cells Improved Cognition in a Diabetic Murine Model - Amin, Shaimaa Nasr; Sharawy, Nivin; El Tablawy, Nashwa; Elberry, Dalia Azmy; Youssef, Mira Farouk; Abdelhady, Ebtehal Gamal; Rashed, Laila Ahmed; Hassan, Sherif Sabry (Frontiers in Physiology, 2021)
Diabetes Mellitus (DM) is a multisystem endocrine disorder affecting the brain. Mesenchymal stem cells (MSCs) pretreated with Melatonin have been shown to increase the potency of MSCs. This work aimed to compare Melatonin, stem cells, and stem cells pretreated with Melatonin on the cognitive functions and markers of synaptic plasticity in an animal model of type I diabetes mellitus (TIDM). Thirty-six rats represented the animal model; six rats for isolation of MSCs and thirty rats were divided into five groups: control, TIDM, TIDM+Melatonin, TIDM+Stem cells, TIDM+ Stem ex Vivo Melatonin. Functional assessment was performed with Histological and biochemical evaluation of hippocampal Neuroligin 1, Sortilin, Brain-Derived Neurotrophic Factor (BDNF), Inducible nitric oxide synthase (iNOS), Toll-like receptor 2 (TLR2), Tumor necrosis factor-alpha (TNF-α), and Growth Associated Protein 43 (GAP43). TIDM group showed a significant decrease of hippocampal Neuroligin, Sortilin, BDNF, and a significant increase in iNOS, TNF-α, TLR2, GAP43. Melatonin or stem cells groups showed improvement compared to the diabetic but not compared to the control group. TIDM+ Stem ex Vivo Melatonin group showed a significant improvement and some values restored to normal. Ex Vivo melatonin treated stem cells had improved spatial working and object recognition memory and depression, improving glucose homeostasis, inflammatory markers, and synaptic plasticity markers.